Differential effects of immaturity and neonatal lung disease on the lung function of very low birth weight infants at 48–52 postconceptional weeks. Issue 12 (8th February 2013) - Schmalisch, Gerd; Wilitzki, Silke; Roehr, Charles C.; Proquitté, Hans; Bührer, Christoph
Abstract Background The pathogenesis of chronic lung disease of prematurity involves maturational arrest and neonatal lung disease (NLD) followed by mechanical ventilation (MV). However, the effect of these factors on postnatal lung function is not well established. Therefore, the aim of this study was to examine the differential effects of immaturity and NLD requiring MV on lung function test (LFT) parameters within 4 months after discharge. Patients and Methods A total of 386 very low birth weight (VLBW) infants (birth weight <1, 500 g) were examined at a median postmenstrual age of 49 weeks. Two hundred twenty‐six infants (59%) were born before the 28th week of gestation, and 247 infants (64%) had NLD requiring invasive MV. LFTs included tidal breathing measurements, measurement of respiratory mechanics assessed by occlusion test, body plethysmography, SF6 multiple breath washout, forced expiratory flow (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3rkx1zkv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VmaxFRC′</alternatives>) by rapid thoraco‐abdominal compression technique, end‐expiratory CO2 (PetCO2), exhaled NO (FeNO), and arterialized capillary blood gas analysis. Main Results Multivariate analysis indicated that severe immaturity was mainly associated with changes in the breathing pattern (reduced tidal volume (P = 0.003) and increased respiratory rate (P = 0.03)), a reduced <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3rkx1znz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VmaxFRC′</alternatives> (P = 0.004) and lower respiratory compliance (P < 0.001). NLD requiring MV, but not immaturity, was significantly and independently associated with increased respiratory and airway resistances (both P = 0.003), reduced FRCSF6 (P = 0.03), increased PetCO2 (P = 0.019) and lower FeNO (P < 0.001). Both immaturity and NLD requiring MV caused a lower paO2 (P < 0.001) and higher a paCO2. Conclusions Lung function after discharge of VLBW infants is differentially affected by both immaturity and NLD requiring MV. With increasing prematurity, intubated and mechanically ventilated infants are at increased risk of developing impaired lung function which can be detected by LFT. Pediatr Pulmonol. 2013; 48:1214–1223. © 2013 Wiley Periodicals, Inc.